2020
DOI: 10.14324/111.444/000047.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of lockdown on activities of daily living in built environment and well-being

Abstract: In an effort to arrest the spread of COVID-19 infection, a nation-wide lockdown was declared in India in March 2020. To assess how personal built environment affected the citizens in the first few weeks, an explorative online survey was conducted, eliciting responses about the work habits before the lockdown, the psychological well-being, time spent in various activities, characteristics of those who worked from home and sleep patterns. The major difference entailed by thelockdown was a reduction of time and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In Nigeria, electricity and water access were deemed essential in individuals' respect of lockdown and in mitigating the pandemic (Gift et al, 2020), although such considerations are not in question in the French context. In India, individuals working from home preferred to do so in the bedroom and students preferred to study outside (Pasala, Gumpeny, Kosuri, Tippana, & Gumpeny, 2020), raising the question of some household affordances (or lack thereof) as a potential hindrance or benefit for teleworking. Going further, D'Alessandro (D'Alessandro et al, 2020) identified five key criteria for housing to benefit well-being during lockdown: visibility and accessibility of green spaces (see also Samuelsson, Barthel, Colding, Macassa, & Giusti, 2020), flexibility so as to favour privacy and avoid crowding, thermal comfort and good indoor air quality, availability of clean drinking water, and adaptability to increased waste production and energy consumption.…”
Section: The Role Of Household Affordancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, electricity and water access were deemed essential in individuals' respect of lockdown and in mitigating the pandemic (Gift et al, 2020), although such considerations are not in question in the French context. In India, individuals working from home preferred to do so in the bedroom and students preferred to study outside (Pasala, Gumpeny, Kosuri, Tippana, & Gumpeny, 2020), raising the question of some household affordances (or lack thereof) as a potential hindrance or benefit for teleworking. Going further, D'Alessandro (D'Alessandro et al, 2020) identified five key criteria for housing to benefit well-being during lockdown: visibility and accessibility of green spaces (see also Samuelsson, Barthel, Colding, Macassa, & Giusti, 2020), flexibility so as to favour privacy and avoid crowding, thermal comfort and good indoor air quality, availability of clean drinking water, and adaptability to increased waste production and energy consumption.…”
Section: The Role Of Household Affordancesmentioning
confidence: 99%
“…Based on the theoretical considerations presented previously, we expected that resilience and coping would be positively linked during lockdown (e.g., Campbell-Sills et al, 2006;Leipold & Greve, 2009;Secades et al, 2016), and that household affordances (e.g., Gift et al, 2020;Pasala et al, 2020) and social position (e.g., Adams-Prassl et al, 2020a;Fortuna et al, 2020) would predict lockdown resilience and coping. Going further, as recent observations have implied that household affordances and social position are linked in relation to the consequences of lockdown (e.g., Chiou & Tucker, 2020;Judge & Rahman, 2020;Rodriguez-Rey et al, 2020), we expected that social position and household affordances would exert an interaction effect on lockdown resilience and coping (Fig.…”
Section: Hypothesesmentioning
confidence: 99%